The association of health behaviors prior to cancer diagnosis and functional aging trajectories after diagnosis: Longitudinal cohort study of middle-aged and older US cancer survivors - Ashly C. Westrick; Kenneth M. Langa; Lindsay C. Kobayashi (Preventive Medicine Reports, 2023)
We aimed to determine the influence of modifiable health behaviors prior to a cancer diagnosis on functional aging trajectories after diagnosis among middle-aged and older cancer survivors in the United States. Data were from biennial interviews with 2,717 survivors of a first incident cancer diagnosis after age 50 in the population-based US Health and Retirement Study from 1998 to 2016. Smoking status, alcohol use, and vigorous physical activity frequency were assessed at the interview prior to cancer diagnosis. Confounder-adjusted multinomial logistic regression was used to determine the associations between each pre-diagnosis health behavior and post-diagnosis trajectories of memory function and limitations to activities of daily living (ADLs), which were identified using group-based trajectory modeling. Overall, 20.7 % of cancer survivors were current smokers, 30.6 % drank alcohol, and 27.1 % engaged in vigorous physical activity >=once a week prior to their diagnosis. In the years following diagnosis, those who had engaged in vigorous physical activity > once a week were less likely to have a medium–high (OR: 0.5; 95 % CI: 0.2–0.9) or medium–low memory loss trajectories (OR: 0.6; 95 % CI: 0.3–1.0) versus very low memory loss trajectory, and were less likely to have a high, increasing ADL limitation trajectory (OR: 0.3; 95 % CI: 0.2, 0.6) versus no ADL limitation trajectory. Vigorous physical activity, but not smoking or alcohol use, was associated with better post-diagnosis functional aging trajectories after a first incident cancer diagnosis in mid-to-later life in this population-based study. Identification of modifiable risk factors can inform targeted interventions to promote healthy aging among cancer survivors.